Fungsi Kontrol Pada Proses Pengembangan Kebijakan, Rekomendasi & Advokasi Kebijakan - Chreisye Kardinalia Fransisca Mandagi; Gracela Partiah Mangngi; Helsa Claudia; Josua Aprilio Sitorus; Kasih Frigia Angel Rumengan; Kevin Vicky Karongkong; Marlina Kessya Moha; Viatika Elizabeth Tias (KOLONI, 2026)
The National Health Insurance Program (Jaminan Kesehatan Nasional/JKN) in Indonesia has achieved a significant milestone by covering 98% of the population as of 2024. However, this quantitative expansion has not been optimally matched by improvements in service quality, health facility readiness, and financial sustainability. Within this ecosystem, the monitoring and evaluation (M&E) function plays a strategic role as a control mechanism in the development of evidence-based policies. Objective: This study aims to comprehensively analyze macro, administrative, clinical, and community-based control functions in the implementation of JKN, as well as to identify gaps in the current M&E system. Methods: This research employs a literature review method of 21 scientific articles published over the past 10 years, sourced from Google Scholar and PubMed databases. Results: The findings indicate that the control functions of JKN currently face challenges such as high institutional fragmentation, inaccuracies in validating data for participants in the informal sector, and increased workload and financial pressures on healthcare facilities due to suboptimal capitation and INA-CBGs tariffs. Additionally, a significant gap was identified in which M&E remains biased toward administrative and quantitative achievements (UHC targets) and has not yet been optimized as a tool for policy learning. Conclusion: The control function of the JKN program needs to transition from a quantity-oriented approach to one focused on equitable service quality. An integrated, information technology-based M&E system orchestrated by cross-sectoral institutions is required, along with strengthened bottom-up, community-based control to ensure the sustainability of the national health system.